Metode Tawa D'lompat (Tanya Jawab Dua Kelompok Debat) untuk Meningkatkan Hasil Belajar Fikih Materi Kurban dan Akikah - Naela Isfiana (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2022)
This study aims to find out how the implementation of the Tawa D’ Lompat method and whether the implementation of the Tawa D’ Lompat method can improve the learning outcomes of Fiqh subjects in the Sacrificial and Akikah materials. The results of the writing obtained that the application of the Tawa D’ Lompat method can improve the learning outcomes of Fiqh subjects . This study used the Test method in obtaining data on research results. The technique used for data analysis in this study is an analytical descriptive technique. Quantitative data obtained from the final test results were processed using percentage descriptions. The results of the writing obtained that the application of the Tawa D’ Lompat method can improve the learning outcomes of Fiqh subjects . The learning outcomes of students before the Tawa D’ Lompat method was implemented were 70.9 with a category less than KKM (KKM 75). And after using the D' JumpIng Laughter Method, the grade point average is 85.0 with good categories.